Dietary Fiber Is Inversely Associated With Depressive Symptoms in Premenopausal Women - Li, Di; Tong, Yongqing; Li, Yan (Frontiers in Neuroscience, 2020)
Background: A inverse association between depressive symptoms and dietary fiber intake was reported in general population, but this association are unstudied in midlife women. This study was designed to investigate the association of dietary fiber intake with depressive symptoms in midlife women. Methods: Data for this cross-sectional study were retrieved from baseline assessment of the Study of Women’s Health Across the Nation (SWAN). Linear regressions were used to examine the association of fiber intake with Center for Epidemiological Studies-Depression (CES-D) score. Logistic regression and restricted cubic spline models were used to examine the association of fiber intake with depressive symptoms (CES-D score≥16). Results: A total of 3054 midlife in our study were stratified into premenopausal women and early perimenopausal women by menstrual bleeding patterns. In premenopausal women, dietary fiber intake was inversely associated with CES-D scores in unadjusted, age-, race/ethnicity-, total family income-, education-, sport-, BMI-, dietary total caloric intake- and use of antidepressant-adjusted and fully adjusted linear regression model. The fully adjusted regression coefficient with 95% confidence intervals (CIs) of fiber intakes was -0.146 (-0.235, -0.058) for CES-D score. Fiber intake was inversely associated with depressive symptoms (CES-D score ≥16) in each logistic regression model. The fully adjusted odds ratios (ORs) with 95% CI of depressive symptoms was 0.483 (0.314–0.745) in quartile 4 compared with quartile 1 for fiber intake. However, in early perimenopausal women, no significant association was observed between dietary fiber intake and depressive symptoms. Conclusion: Dietary fiber may be inversely associated with depressive symptoms in premenopausal women, but not in early perimenopausal women.